2005
DOI: 10.1007/s00234-005-1397-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative MRI to guide the resection of primary supratentorial glioblastoma multiforme—a quantitative radiological analysis

Abstract: Patients with supratentorial high-grade glioma underwent surgery within a vertically open 0.5-T magnetic resonance (MR) system to evaluate the efficacy of intraoperative MR guidance in achieving gross-total resection. For 31 patients, preoperative clinical data and MR findings were consistent with the putative diagnosis of a high-grade glioma, in 23 cases in eloquent regions. Tumor resections were carried out within a 0.5-T MR SIGNA SP/i (GE Medical Systems, USA). The resection of the lesion was carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(58 citation statements)
references
References 52 publications
1
52
0
4
Order By: Relevance
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, efforts have been made in recent years to integrate DTI data with neurosurgical navigation systems , Coenen et al 2003, Talos et al 2003, Berman et al 2004, Shinoura et al 2005, Nimsky et al 2006. Such a study on the role of diffusion tensor imaging of the corticospinal tract (CST) before and after mass resection, and the correlations with clinical motor findings, was recently published by Laundre et al 2005. Interventional MRI (iMRI) has proven to be an effective tool for improving the completeness of low grade glioma resection (Claus et al 2005, Bradley 2002, Schneider et al 2001, Schneider et al 2005, Knauth et al 1999, Wirtz et al 2000. However, brain deformations typically occur during the neurosurgical procedure, which results in a misalignment between the pre-operatively acquired datasets and the intraoperative brain position.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,25,38) The findings of intraoperative imaging modified the surgical strategy in 71.1% of patients with gliomas, the highest among our cases of brain tumors, indicating that glioma surgery was the best indication.…”
Section: Discussionmentioning
confidence: 78%